Variacion somaclonal en seis genotipos de arroz - Torrealba, G.=700 1 Salazar, E.; Alvarez, R.; Delgado, N.; Figueroa, R.; Moreno, O.; Castrillo, W.; Reyes, E.; Torres, O.; Navas, M.; Salazar, M.
(En, Es)
ilus., 5 ref.
Keywords: ORYZA SATIVA; VARIACION SOMACLONAL; VENEZUELA; AGRONOMIA TROPICAL